Restoring a post-traumatic partial edentulous mandible with the Toronto prosthesis: a clinical report - Fatemeh Nematollahi; Marzieh Alikhasi; Elaheh Beyabanaki (Tabriz University of Medical Sciences, 2018)
Implants provide support, stability and retention for restorations used in fully and partially edentulous patients. This clinical report describes prosthetic treatment of a 30-year-old man suffering from a dentoalveolar deficiency due to an old gunshot trauma to the left side of the mandible. The patient was rehabilitated with implant-supported Toronto prosthesis following surgical placement of three implants with undesirable location and angulations due to lack of sufficient bone. This prosthetic option offers advantages of both screw-retained and cement-retained prostheses and provides acceptable aesthetic and functional results.